Oxidative dehydrogenation of ethyl benzene to styrene over hydrotalcite derived cerium containing mixed metal oxides - Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Kaliyappan, Periyasamy; Raja, Thirumalaiswamy (Green Chemistry, 2013)
Cerium containing mixed oxides derived from hydrotalcites was prepared and its catalytic activity was studied for oxidative dehydrogenation of ethyl benzene to styrene. Structural, spectroscopic and morphological features of the catalyst have been thoroughly examined with various physico-chemical characterization methods. Raman spectroscopy studies show evidence for oxygen vacancies in lower loadings of cerium which enhanced the oxygen migration. The transmission electron microscopy image showed good dispersion of ceria clusters on the mixed metal oxide. The catalytic activity results suggested that the conversion of ethyl benzene and styrene yield is stable for at least 12 hours without any significant catalyst deactivation. The styrene selectivity and ethyl benzene conversion were higher in a catalyst containing 0.03 mole percentage of cerium. Structural features of the spent catalysts have also been examined to demonstrate the stability of the catalyst during the reaction.